Health Education on the Dangers of Smoking and the Importance of Breakfast for Outsourced Workers at BPJS Kesehatan Samarinda Branch Office: Edukasi Bahaya Merokok dan Pentingnya Sarapan bagi Tenaga Alih Daya di BPJS Kesehatan KC Samarinda - Fadlillah, Muhammad Ridho; Wisnuwardani, Ratih Wirapuspita; K, Iriyani; Rizki, Agung Tribawa; Gifari, Muhammad Tijar (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
This community service project aimed to enhance the knowledge of outsourced workers at BPJS Kesehatan’s Samarinda Branch Office regarding the health risks associated with smoking and the importance of maintaining a nutritious breakfast routine. Initial data revealed prevalent unhealthy habits, including high smoking rates and irregular breakfast patterns among workers, which can adversely impact their productivity and long-term health. The intervention involved structured health education sessions, including presentations and interactive discussions, focusing on the adverse effects of smoking and the benefits of a healthy breakfast for sustaining energy and concentration. Pre-test and post-test assessments were conducted to measure knowledge improvement, and results showed a statistically significant increase in post-intervention scores (p = 0.029). These findings underscore the positive impact of targeted health education in promoting healthier habits among outsourced workers, contributing to better workplace well-being and productivity.